Use of bath paraffin and exercise for individuals with intermittent claudication - a pilot study - Carvalho, Maria Luíza Vieira; Fonseca, Julia Baumgratz Tahan; Angelo, Eduardo Frederico Cherem Ferreira; Lobato, Thiago; Pereira, Danielle Aparecida Gomes; da Cunha-Filho, Inácio Teixeira (Journal of Respiratory and CardioVascular Physical Therapy, 2013)
Background: Peripheral arterial obstructive disease's (PAOD) most common symptom is the Intermittent Claudication. The hot paraffin associated with physical exercise could be a possible support in the treatment of PAOD patients, since the amount of heat delivered to the tissues may potentially increase blood flow. Objectives: compare the indicators of functional capacity between a group of individuals with PAOD who underwent a combination of thermal stress and physical exercise, and another group of similar individuals treated only with physical exercise. Methods: Paraffin Group (PG) comprised of 10 individuals received thermal stress (hot compresses of paraffin) before physical activity. The control group (CG) of 9 participants was treated with physical activity alone. Shuttle-walking test (SWT), six-minutes walking test (6MWT) and ankle-brachial index (ABI) before interventions and after six weeks of training were assessed. Results: The mean age of the PG and for CG was 59.1 ± 10.41 and 68.89 ± 4.91 years (p = 0,019), BMI 27.54 ± 3,52 and 27.51 ± 2,07 (p=0,98) respectively. There was no statistically significant difference in the mean values of distance, time, speed or walking economy, both at symptom onset and at limiting symptom between groups during the SWT (p > 0,05). The change in distance measured during the 6MWT, both at symptom onset and at limiting symptom were not different between groups (p > 0,05). Conclusion: There was no statistically significantly difference in the indicators of functional capacity between PG and CG.